Did long‐term fire control the coniferous boreal forest composition of the northern Ural region (Komi Republic, Russia)?. (16th August 2020) - Barhoumi, Chéïma; Ali, Adam A.; Peyron, Odile; Dugerdil, Lucas; Borisova, Olga; Golubeva, Yulia; Subetto, Dmitri; Kryshen, Alexander; Drobyshev, Igor; Ryzhkova, Nina; Joannin, Sébastien
Abstract: Aim: Documenting past vegetation dynamics and fire‐vegetation relationships at a regional scale is necessary to understand the mechanisms that control the functioning of the boreal forest, which is particularly sensitive to climate change. The objective of this study is to document these interactions in the Komi Republic during the Holocene. Location: Yaksha, Vychegda river basin, Republic of Komi, Russia. Taxon: Plantae, gymnosperms, angiosperms. Methods: Two palaeoecological approaches are combined, based (1) on pollen (this study) and charcoal analysis (recomputed from our previous analysis) applied to cores from two peatlands and (2) on a REVEALS model (a part of the Landscape Reconstruction Algorithm "LRA") applied to six regional pollen cores in order to obtain a regional estimate of vegetation cover during the Holocene. Results: The pollen diagram produced locally from Yaksha was compared with the regional vegetation cover determined by REVEALS. Taxa such as Abies sp. and Pinus spp. showed differences between the two approaches, but vegetation signals remain qualitatively consistent. From 10, 000 to 6, 000 cal. yr BP, the forest was mainly a light taiga (composed of Pinus sylvestris and Betula spp.) and low fire activity was recorded. From 6, 000 to 3, 500 cal. yr BP, a dark taiga (composed of Picea spp., Abies sibirica and Pinus sibirica ) was established due to favourable climatic conditions, despite higher fire activity. From 3, 500 cal. yr BP onwards, the continuous increase in fire activity allowed for a gradual return of light taiga, Betula spp., likely reinforced by human activities. The dynamics of Picea spp. and Abie s sp. were asynchronous between the sites. For Picea spp., the hypothesis of local inter‐site expansion distributed along stream corridors is supported by the data. For Abies sp., a bias in REVEALS, and in climate cooling may explain disparities between sites. Main conclusions: We found evidence that in the early and mid‐Holocene, vegetation dynamics were probably more influenced by climate, as fire activity was low. During the late Holocene, fire activity and geomorphology, eventually augmented by human activities, increased in influence on vegetation dynamics and led to the predominance of the light taiga forest up to the present.